5-HT1A autoreceptor in dorsal raphe nucleus mediates sensitization of conditioned place preference to cocaine in mice experienced with chronic pain. Issue 9 (12th June 2019) - Li, Yongfeng; Zhu, Jianyu; Zheng, Qiaohua; Qian, Zhaoqiang; Zhang, Lizi; Wei, Chunling; Han, Jing; Liu, Zhiqiang; Ren, Wei
Abstract : Chronic stress, including chronic neuropathic pain, cannot only induce depressive disorders but also enhance sensitization to addictive drugs. Ample evidence support the implication of the 5-hydroxytryptamine (5-HT) system in the enhanced sensitization to cocaine. However, mechanisms underpinning such an enhancement are still unclear. By using a neuropathic pain model and a combination of behavioral, neurochemical, and western blotting techniques, this study reveals that the mice experienced with chronic neuropathic pain express both depression-like disorders and significant conditioned place preference to cocaine. The conditioned place preference to cocaine and was abolished by administration of the 5-HT1A receptor antagonist into the dorsal raphe nucleus (DRN). The expression of DRN 5-HT1A receptor was upregulated in mice experienced with chronic neuropathic pain. Moreover, such an upregulation was restored by repeated exposure to cocaine. The results reveal that DRN 5-HT1A receptor mediate the sensitization to cocaine in mice experienced with chronic pain and may be used as a new molecular target for therapeutic interventions to drug addiction influenced by chronic stress.